Metal-Free Synthesis of N-Heterocycles via Intramolecular Electrochemical C-H Aminations - Wang, Huiqiao; Zheng, Yongjun; Xu, Hucheng; Zou, Jiaru; Jin, Congrui (Frontiers in Chemistry, 2022)
N-heterocycles are key structural units in many drugs, biologically interesting molecules and functional materials. To avoid the residues of metal catalysts, the construction of N-heterocycles under metal-free conditions has attracted much research attention in academia and industry. Among them, the intramolecular electrochemical C-H aminations arguably constitute environmentally friendly methodologies for the metal-free construction of N-heterocycles, mainly due to the direct use of clean electricity as the redox agents. With the recent renaissance of organic electrosynthesis, the intramolecular electrochemical C-H aminations have undergone much progress in recent years. In this article, we would like to summarize the advances in this research field since 2019. The emphasis is placed on the reaction design and mechanistic insight. The challenges and future developments in the intramolecular electrochemical C-H aminations are also discussed.